Implementasi Teknologi Climate Smart Agriculture (CSA) dalam Meningkatkan Produktivitas Pertanian di Kabupaten Nagekeo - Veradiana Bewo; Nursalam Nursalam; Rouwland A. Benyamin; Mariayani O. Rene (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the implementation of Climate Smart Agriculture (CSA) technology in improving agricultural productivity in Nagekeo Regency. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving informants from the Department of Agriculture, agricultural extension workers, farmers, and community members. Data analysis used the interactive model of Miles and Huberman, while the policy implementation analysis applied George C. Edward III’s framework, which includes communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of CSA in Nagekeo Regency has been carried out through socialization, training, and field assistance for farmers. However, its implementation has not been optimal due to several constraints, including communication barriers, limited human resources, and weak institutional coordination. In addition, some farmers are still hesitant to adopt new technologies due to conventional farming practices, limited knowledge, and farming risks. Therefore, strengthening policy communication, improving farmers’ capacity, intensifying extension services, and enhancing institutional coordination are necessary to ensure the effective and sustainable implementation of CSA.